(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article is devoted to the study of Friendship, what is the deep, miraculous meaning of it and what kind friendships do we have, how can people find and differentiate the real friends, how to show affection to your friends, long-lasting friendship leads people to beautiful life and some more quotes and proverbs about friends and frienship.